2006
DOI: 10.2527/jas.2006-154
|View full text |Cite
|
Sign up to set email alerts
|

In vivo estimation of sheep carcass composition using real-time ultrasound with two probes of 5 and 7.5 MHz and image analysis1

Abstract: Ultrasonic measurements were taken on 46 sheep using a real-time ultrasound machine equipped with 2 probes (5 and 7.5 MHz). Measurements of subcutaneous fat thickness (SC) and muscle LM depth (MD) and area (MA) were taken at 2 locations: over the 13th thoracic vertebra (SC13, MD13, and MA13, respectively) and at the interval between the third and fourth lumbar vertebrae (SC34, MD34, and MA34, respectively). Fat thickness was also measured over the third sternebra of the sternum. The relationship between carcas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
8
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 18 publications
8
58
8
2
Order By: Relevance
“…Emenheiser et al (27) similarly reported that UFT and carcass fat amount variations were greater than those of other traits. In another study on sheep and male lambs, Silva et al (20) reported that fat thickness, which had a variation of 62%, had the greatest variation value.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emenheiser et al (27) similarly reported that UFT and carcass fat amount variations were greater than those of other traits. In another study on sheep and male lambs, Silva et al (20) reported that fat thickness, which had a variation of 62%, had the greatest variation value.…”
Section: Discussionmentioning
confidence: 99%
“…They also reported that carcass fat amount could be determined with only the UFT measurement (R 2 = 69%-70%), and that the carcass bone amount might be estimated only with live weight (R 2 = 52%-81%). Silva et al (20) remarked that muscle amount estimation (R 2 = 99%) may be made with live weight in conjunction with UFT and ULD values taken from the 12-13T region, and that live weight and UFT may be used to predict total fat amount (R 2 = 98%). There is no statistically significant regression equation for predicting the chemical composition of the carcass from the USF, UFT, ULD, ULW, and ULA values taken from 12-13T and 3-4L in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A utilização da ultrassonografia tem se mostrado uma téc-nica eficiente para avalivar a gordura subcutânea in vivo, a deposição muscular; bem como estimar a qualidade e a composição da carcaça (Silva et al, 2003); permitindo prever o momento ideal do abate (Teixeira et al, 2008). Estudos em caprinos (Teixeira et al, 2008), ovinos (Silva et al, 2006, Teixeira et al, 2006, suínos (Dutra Jr. et al, 2001) e bovinos (Prado et al, 2004) têm demonstrado uma correlação altamente significativa entre as medidas realizadas por meio da ultrassonografia e as realizadas na carcaça, tornando-se uma técnica de elevada precisão para predizer a composição da carcaça.…”
Section: Variávelunclassified
“…The US has also been used to study intramuscular fat in live pigs (Newcom et al, 2002) and in other species, such in cattle to study the repeatability and accuracy of US in measuring backfat (Brethour, 1992) and sheep to study estimation of sheep carcass composition using real-time ultrasound (Silva et al, 2006). It has been similarly used, either in vivo or post mortem, to estimate raw meat quality characteristics, mainly intramuscular fat, with the highest reported R 2 of 0.92 in pork (Newcom et al, 2002).…”
Section: A) Visual Image Analysis By Monitoringmentioning
confidence: 99%